ANALISIS SENTIMEN UNTUK MEMPREDIKSI PENGARUH PENGGUNAAN GADGET TERHADAP PENDIDIKAN DENGAN METODE NAIVE BAYES - Hutagalung, Isnaini; Koko Handoko (Computer Science and Industrial Engineering, 2024)
In this age of rapid technological development, everyone including children needs access to communication and information technology. One of the electronic devices that people use to communicate is gadgets. People also often use gadgets for business, social media, news, and human resources. It is true that we often see adults, the elderly (60 years old and above), and teenagers (12-21 years old) using multiple gadgets. More ironically, these devices are also often used and given to toddlers (1-5 years old), who should not have them yet, but are given by their parents to keep their children from crying. Therefore, we will use data mining techniques combined with the Naive Bayes approach to conduct this research. The Naive Bayes method is one of the strategies used in data mining to classify data. The results of the study are based on the amount of time students spend in using devices for learning that has been recorded and then analyzed using the RapidMiner application with the Naive Bayes method